2016
DOI: 10.1007/s10499-016-0043-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antibacterial activity of two different sizes of colloidal silver nanoparticle (cAgNPs) against Vibrio harveyi isolated from shrimp Litopenaeus vannamei

Abstract: Silver nanoparticles are the most important nanomaterials for antibacterial uses and are famous for their strong inhibitory and antibacterial effects. In recent years, extensive studies have been undertaken on the use of antimicrobial properties of silver, incorporated within aquaculture industry. To evaluate the scientific basis for the use of the nano silver in shrimp aquaculture, in this study the antimicrobial activities of colloidal nano silver with two different sizes (16.62 and 22.22 nm) was evaluated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The improved growth performance as seen in this study occurred because silica in nanoform may function as the nutrient carrier (especially for amino acids). These hauled nutrients could have further contributed to increasing the digestion and absorption of nutrient molecules through the controlled encapsulation and release of nutrients from the gastrointestinal tract to the bloodstream (Bahabadi et al, 2017). This increase could also be correlated with the amelioration of DNA and RNA syntheses and an improvement in gut microorganisms, which are supported by NPs (Onuegbu et al, 2018); however, this warrants a further investigation with silica NPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improved growth performance as seen in this study occurred because silica in nanoform may function as the nutrient carrier (especially for amino acids). These hauled nutrients could have further contributed to increasing the digestion and absorption of nutrient molecules through the controlled encapsulation and release of nutrients from the gastrointestinal tract to the bloodstream (Bahabadi et al, 2017). This increase could also be correlated with the amelioration of DNA and RNA syntheses and an improvement in gut microorganisms, which are supported by NPs (Onuegbu et al, 2018); however, this warrants a further investigation with silica NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Silica NP was incorporated into diets at levels of 0 mg/Kg (T0), 1 mg/Kg (T1), 2 mg/kg (T2), and 3 mg/Kg (T3). As an innate marker, 0.05% Cr 2 O 3 was incorporated into diets for the further determination of the digestibility of tilapia according to Austreng (1978). The proximate compositions of the ingredients and diets were analyzed before and after the formulation of diets (Table 1), respectively, according to AOAC (2005) (for details, as shown in section Proximate Composition of Fish Muscle).…”
Section: Diet Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results showed that smaller AgNPs had greater antibacterial activity against V. harveyi than larger nanoparticles. According to the findings of the study, AgNPs have potential as antibacterial agents for reducing bacteria growth [ 64 ]. The study by Huq [ 65 ] found that AgNPs produced using Lysinibacillus xylanilyticus strain MAHUQ-40 could be used as an antibacterial agent.…”
Section: Nanoparticlesmentioning
confidence: 99%